Analysis of migration processes and assessment of their impact on the development of international money transfers of Ukraine - Kolupaieva, I.; Shevchenko, O.; Mytsenko, I.; Borysova, A.; Колупаєва, І. В.; Шевченко, О. О.; Миценко, І. М.; Борисова, А. О. (Masaryk University, 2019)
The main purpose of the research is to analyse migration processes of Ukraine and to determine the factors influencing the development of the market of international money transfers in Ukraine as a significant direction of strengthening the financial system of the country.
Аналіз міграційних процесів та оцінка їх впливу на розвиток міжнародних грошових переказів України
Keywords: migration policy; international money transfers; financial system; transmission; money transfer channel